Prevalence of domestic accidents in the rural field practice area of a medical college in Bangalore, Karnataka - N R Ramesh Masthi; S G Kishore; Gangaboriah (Wolters Kluwer Medknow Publications, 2012)
Domestic accidents are worldwide health problems. A cross-sectional study was conducted in the rural field practice area of Kempegowda Institute of Medical Sciences, Bangalore. A total of 5419 individuals were selected from 30 clusters (villages) using cluster sampling technique. Of the 5419 study population, 50.9% (2748) were males and the rest were females. The prevalence of domestic accidents in the rural community was found to be 9.6% (522 individuals who had sustained domestic accidents), was found to be more in females compared with males, which was statistically significant with P-value =0.0077 (Z value =9.09). Falls 43% (225) was the most common type of domestic accidents. The most common place of occurrence of domestic accidents was 46% (243) kitchen, most frequent site of injures in domestic accidents was upper limbs.